The Effect of Capital Structure, Profitability, and Liquidity on Company Value - Irza Ayu Salsabilla; Suhardi Suhardi (Economic: Journal Economic and Business, 2025)
This study examines the influence of capital structure, profitability, and liquidity on the valuation of companies in the construction industry listed on the Indonesia Stock Exchange (IDX) for the period from 2020 to 2024. Using a quantitative methodology, this study employs panel data regression along with a Random Effects Model estimation technique, drawing on secondary data from 22 construction companies that met the established sampling criteria over a five-year observation period. The findings reveal that, separately, capital structure has a negative but statistically insignificant impact on firm valuation. Conversely, profitability exhibits a negative and statistically significant effect on firm value, while liquidity exhibits a positive and statistically significant effect on firm valuation. Collectively, the three independent variables significantly influence firm valuation. These results suggest that investors prioritize firm liquidity when evaluating the prospects and value of construction companies. Conversely, high profitability does not consistently correlate with increased firm value, potentially due to market perceptions regarding the quality of earnings generated. The implications of this study underscore the need for company management to prioritize liquidity management and improve financial information transparency to enhance firm value from an investor perspective.